Supercritical water gasification of microalga Chlorella vulgaris over supported Ru - Tiong, L. (2019)
Catalytic gasification of microalgae (Chlorella vulgaris) was performed in supercritical water (SCW) at 385 Â°C and 26 MPa in a stainless steel batch reactor with various supported Ru as catalysts, and the gasification characteristics was examined in detail. With Ru/charcoal catalyst and at 4.8 wt solid feed concentration, total gas conversion of C. vulgaris organic matter reached its plateau of 87 C gasification within 30 min reaction time. Gasification rate was strongly dependent on Ru particle size, whereas product distribution within the gas components showed more influence of catalyst support material. Ru/charcoal catalyst kept its activity in the first three repetitive runs, then gradually lost its activity to ca. half of its original activity after 5th run, while Ru kept its metallic state throughout. Loss of Ru metal after 1 h of SCW gasification was found to be ca. 0.017 of charged amount. Â© 2018 Elsevier B.V.